Study of W boson production in pPb collisions at root(NN)-N-S=5.02 TeV - (:unkn) unknown (ELSEVIER, 2015)
The first study of W boson production in pPb collisions is presented, for bosons decaying to a muon or electron, and a neutrino. The measurements are based on a data sample corresponding to an integrated luminosity of 34.6 nb(-1) at a nucleon-nucleon centre-of-mass energy of root(NN)-N-S = 5.02 TeV, collected by the CMS experiment. The W boson differential cross sections, lepton charge asymmetry, and forward-backward asymmetries are measured for leptons of transverse momentum exceeding 25 GeV/c, and as a function of the lepton pseudorapidity in the vertical bar eta(lab)vertical bar < 2.4 range. Deviations from the expectations based on currently available parton distribution functions are observed, showing the need for including W boson data in nuclear parton distribution global fits. (C) 2015 CERN for the benefit of the CMS Collaboration. Published by Elsevier B.V.
Keywords: CMS; W boson; pPb collisions; PARTON